2022
DOI: 10.55976/cds.1202216617-23
|View full text |Cite
|
Sign up to set email alerts
|

A study on the beneficial evidence and mechanism of the therapeutic effect of dapagliflozin on heart failure

Abstract: Heart failure (HF) is the final manifestation of various cardiovascular (CV) diseases, which has caused a huge health burden. Although great progress has been made in the treatment strategy, it still cannot solve the dilemma of HF treatment. As a sodium glucose transporter 2 inhibitor, dapagliflozin is a hypoglycemic drug. However, recent research has found that it can play a crucial role in preventing HF, regardless of whether patients have diabetes or not. There are many mechanisms involved, so this review f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The pathological changes in MIRI mainly include inflammatory reaction, endothelial cell injury, blood flow disorder, expansion of myocardial infarction area caused by necrosis and apoptosis of cardiomyocytes, reperfusion arrhythmia, myocardial stunning, and coronary microcirculation disorder; MIRI can lead to heart failure, and seriously threaten the patients' lives. [13][14][15] As a kind of bisepoxylignans, PDG has the function of protecting cells from oxidative damage. It is reported that PDG can reduce neuroinflammation, neuronal apoptosis, and oxidative stress through modulating Toll-like receptor 4 and heme oxygenase 1 (HO-1) pathways in a mice model with AD.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological changes in MIRI mainly include inflammatory reaction, endothelial cell injury, blood flow disorder, expansion of myocardial infarction area caused by necrosis and apoptosis of cardiomyocytes, reperfusion arrhythmia, myocardial stunning, and coronary microcirculation disorder; MIRI can lead to heart failure, and seriously threaten the patients' lives. [13][14][15] As a kind of bisepoxylignans, PDG has the function of protecting cells from oxidative damage. It is reported that PDG can reduce neuroinflammation, neuronal apoptosis, and oxidative stress through modulating Toll-like receptor 4 and heme oxygenase 1 (HO-1) pathways in a mice model with AD.…”
Section: Discussionmentioning
confidence: 99%